Stability analysis of recurrent type-2 TSK fuzzy systems with nonlinear consequent part. Issue 1 (January 2017) - Tavoosi, Jafar; Suratgar, Amir; Menhaj, Mohammad
Abstract A necessary condition for stability of a class of recurrent type-2 TSK fuzzy systems is presented. In this system, the antecedent part is indeed represented by interval Gaussian type-2 fuzzy set, and the consequent part is an ordinary nonlinear function of the system's inputs. In the proposed method, at first a type-2 fuzzy model is established, and then an LMI-based stability analysis of the model is fully discussed. Two first-order systems (one stable and one unstable) and two second-order systems (one stable and one unstable) are then considered as proper case studies. The simulation results easily approve the effectiveness of the proposed method.